2009
DOI: 10.1111/j.1095-8649.2009.02391.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional connectivity of marine fishes within a semi‐enclosed Newfoundland fjord

Abstract: The interplay between structural connectivity (i.e. habitat continuity) and functional connectivity (i.e. dispersal probability) in marine fishes was examined in a coastal fjord (Holyrood Pond, Newfoundland, Canada) that is completely isolated from the North Atlantic Ocean for most of the year. Genetic differentiation was described in three species (rainbow smelt Osmerus mordax, white hake Urophycis tenuis and Atlantic cod Gadus morhua) with contrasting life histories using seven to 10 microsatellite loci and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 63 publications
(93 reference statements)
0
4
0
Order By: Relevance
“…temperature, salinity, oxygen, pH, and nutrients) have been proposed as causes of trophic and reproductive adaptation [ 27 29 ], and transport and retention of larvae [ 30 , 31 ]. Also, other studies have found population genetics differentiation between inner and outer fjords waters [ 25 , 32 , 33 ]. In such cases, oceanographic features can be a barrier to dispersal at different ontogenetic stages, by restricting gene flow and increasing intraspecific divergence.…”
Section: Introductionmentioning
confidence: 92%
“…temperature, salinity, oxygen, pH, and nutrients) have been proposed as causes of trophic and reproductive adaptation [ 27 29 ], and transport and retention of larvae [ 30 , 31 ]. Also, other studies have found population genetics differentiation between inner and outer fjords waters [ 25 , 32 , 33 ]. In such cases, oceanographic features can be a barrier to dispersal at different ontogenetic stages, by restricting gene flow and increasing intraspecific divergence.…”
Section: Introductionmentioning
confidence: 92%
“…Connectivity, a basic concept in topology, is broadly defined in ecology as the physical, chemical and biological processes and their interactions among ecosystems at all levels of the Earth, that is, ecological connectivity (Nagelkerken, 2009; Sheaves, 2009; White & Kiester, 2008). Some researchers divide ecological connectivity into landscape connectivity and patch connectivity based on the concept of landscape ecology, while most ecologists divide it into structural connectivity and functional connectivity (Bradbury et al, 2009; Du et al, 2015; Tischendorf & Fahrig, 2014). Fang reviewed the definitions of ecological connectivity by many researchers and concluded that (1) ecological connectivity is based on species composition between habitats; (2) species can perceive different habitats through lateral, vertical, large and small‐scale daily activities or seasonal migration; and (3) environmental changes in habitats will affect the flow of ecological resources among patches (Fang et al, 2018; Tischendorf & Fahrig, 2014).…”
Section: Ecological Connectivity and Habitat Connectivitymentioning
confidence: 99%
“…Connectivity, a basic concept in topology, is broadly defined in ecology as the physical, chemical and biological processes and their interactions among ecosystems at all levels of the Earth, that is, ecological connectivity [31,32]. Some researchers divide ecological connectivity into landscape connectivity and patch connectivity, while most ecologists divide it into structural connectivity and functional connectivity [28,33,34]. Fang reviewed the definitions of ecological connectivity by many researchers and concluded that (1) ecological connectivity is based on species composition between habitats; (2) species can perceive different habitats through lateral, vertical, large and small-scale daily activities or seasonal migration; and (3) environmental changes in habitats will affect the flow of ecological resources among patches [33,35].…”
Section: Ecological Connectivity and Habitat Connectivitymentioning
confidence: 99%